Fibroblast Fatty-Acid Oxidation Flux Assays Stratify Risk in Newborns with Presumptive-Positive Results on Screening for Very-Long Chain Acyl-CoA Dehydrogenase Deficiency - Simon E. Olpin; Shirley Clark; Jane Dalley; Brage S. Andresen; Joanne Croft; Camilla A. Scott; Aneal Khan; Richard J. Kirk; Rebecca Sparkes; Marisa Chard; Alicia Chan; Emma Glamuzina; et al. (MDPI AG, 2017)
Very-long chain acyl-CoA dehydrogenase deficiency (VLCADD) is a clinically heterogeneous disorder with three major phenotypes: severe neonatal/infantile, milder childhood and late onset myopathic. VLCADD is genetically heterogeneous with numerous pathogenic mutations and variants of uncertain significance. VLCADD is included in many newborn screening programs but these suffer from high false positive rates, primarily due to positive screens in heterozygotes. Separating these and newborns with two low-risk "mild" variants from clinically at risk patients can be problematic, as clinical and biochemical markers are often unreliable, particularly in stable neonates. We have measured fibroblast fatty acid oxidation flux using [9,10-H3]myristic acid and [9,10-H3]oleic acid from 69 clinically presenting VLCADD patients including myopathic and infantile phenotypes and 13 positive newborn screened patients. We also measured fibroblast VLCADD enzyme activity by UV-HPLC detection of product in a sub-set of patients and compared these results to oleate FAO-flux. Fibroblast enzyme assay by UV-HPLC detection failed to clearly discriminate between some clinically presenting VLCADD patient cell lines and cell lines from some simple heterozygotes. FAO-flux clearly discriminated between clinically presenting VLCADD patients and the false positive screened patients. FAO-flux at 37 °C provides information as to the likely clinical phenotype but FAO-flux at 41 °C is the best discriminator for identifying clinically at risk patients.